Trends in atrial fibrillation and flutter mortality associated with disorders of thyroid gland in the United States from 1999 to 2020 - Shahzaib Ahmed; Shoaib Ahmad; Hamza Ashraf; Eeman Ahmad; Umar Akram; Abbas H. Mallick; Irfan Ullah; Raheel Ahmed; Chadi Alraies; Gregg C. Fonarow (Journal of Arrhythmia, 2025)
Abstract Background Thyroid gland disorders are a known risk factor for atrial fibrillation and flutter (AF/AFL). Despite being a well‐established risk factor, most studies have primarily examined prevalence, comorbidities, and treatment patterns with little to no research on mortality trends for this association. Objective: We aimed to analyze the trends in AF/AFL‐related mortality in patients with thyroid gland disorders. Methods Age‐adjusted mortality rates and crude rates per 100,000 population from 1999 to 2020 using the CDC WONDER database. Annual percent changes and their averages were calculated via Joinpoint regression. AF/AFL‐related mortality trends in patients with thyroid disorders were compared with those in the general population using pairwise comparison. Results In the study period, a total of 7187 AF/AFL‐related deaths were observed in individuals diagnosed with thyroid gland disorders. The age‐adjusted mortality rates increased throughout the study period. The mortality rates in females remained consistently higher than those in males. Mortality rates did not vary substantially across regions (South: 0.09; Northeast: 0.09; Midwest: 0.10; West: 0.11). Furthermore, the annual percent change in females and South with thyroid disorders differed significantly from the general population. The states with the highest mortality rates were Oregon, Wyoming, and Nebraska. The mortality rates remained higher in nonmetropolitan regions (0.11) than in metropolitan regions (0.09). Conclusions AF/AFL‐related mortality trends associated with thyroid disorders increased from 1999 to 2020. Policies that target vulnerable populations and regions may be beneficial in mitigating the increasing AF/AFL‐related mortality associated with disorders of the thyroid gland.